Analisis Peningkatan Kualitas Pelayanan Untuk Meningkatkan Kepuasan Konsumen Pada Alfamart Sidoyoso Kota Surabaya - Syafitri, Laras Adriani (Politeknik Negeri Padang, 2022)
The purpose of this study is to determine and analyze the level of importance (Importance) and satisfaction (Satisfaction) of consumers on the quality of service in a company and to determine the attributes that are priority improvements to improve service quality at Alfamart Sidoyoso Surabaya City. The method used in this research is quantitative. The population in this study are consumers who visit and buy at Alfamart Sidoyoso, Surabaya City with at least one purchase and are aged 15-64 years. The samples used in this study were 100 respondents. There are five dimensions of service quality which include Reliability, Responsiveness, Assurance, Empathy, Tangible, which are analyzed through Importance Performance Analysis (IPA) and Potential Gain in Customer Value (PGCV). Based on the results of the analysis that has been carried out on twenty indicators, it is known that there are 4 indicators that must be improved, namely safe parking lots, employees are able to handle complaints and problems quickly, cleanliness of Alfamart Sidoyoso outlets, employees respond to consumer requests quickly.